Pengaruh Pembiayaan Mudharabah dan Musyarakah terhadap Profitabilitas pada Bank Umum Syariah Periode 2019–2024 - Amelia Kinanti Rizky Pratiwi; Khairiyani Khairiyani (ARZUSIN, 2025)
This study is motivated by the inconsistent contribution of profit-and-loss sharing (PLS) financing to the profitability of Islamic banks in Indonesia, despite this scheme being central to the principles of Islamic finance. The research aims to analyze the effect of mudharabah and musyarakah financing on the profitability of Islamic commercial banks in Indonesia during the 2019–2024 period. A quantitative approach with an associative research design was applied. The sample consisted of six Islamic commercial banks—Bank Muamalat Syariah, Bank Victoria Syariah, Bank Mega Syariah, Bank Panin Dubai Syariah, Bank Syariah Bukopin, and BCA Syariah—selected using purposive sampling based on the completeness of financial reports over the observation period. Secondary data were obtained from financial reports published by the Financial Services Authority (OJK) and analyzed using EViews 12 software through panel data regression models, including Common Effect, Fixed Effect, and Random Effect models. The best-fit model was determined through the Chow test, Hausman test, and Lagrange Multiplier test. Hypothesis testing was conducted using t-tests, F-tests, and the coefficient of determination (R²). The results indicate that mudharabah and musyarakah financing, both simultaneously and partially, do not have a significant effect on the profitability (ROA) of Islamic banks. This conclusion suggests that during the study period, profit-and-loss sharing financing had yet to become a key determinant in driving the profitability of Islamic banks in Indonesia.